Pengaruh Gaya Mengajar dan Authentic Assessment terhadap Hasil Belajar IPS Siswa - Cecep Sofyan; Nafan Tarihoran; Diki (Ibtida'i, 2026)
Social Studies (IPS) learning in elementary schools requires active learning processes and assessment methods that comprehensively reflect students’ abilities. However, classroom practices are still dominated by classical teaching styles and conventional assessments, which are less effective in improving students’ learning outcomes. This study aims to analyze the effect of teaching styles and authentic assessment on students’ Social Studies learning outcomes. The study employed a quantitative approach using a 2×2 factorial design. This study included 100 sixth-grade students from public elementary schools located in Banjarsari District, Lebak Regency as the research participants. The results indicate that teaching style has a significant effect on learning outcomes; there is an interaction between teaching style and assessment method; and the combination of an interactional teaching style and authentic assessment produces the highest learning outcomes. These findings suggest that alignment between instructional strategies and assessment methods is important for improving students’ learning outcomes.